Effects of different selenium fertilizer types and dosages on non-volatile organic acids and aroma substances of flue-cured tobacco - Wanhui Jiang; Zijun Sun; Huaiyuan Li; Yaoxing Liang; Qihang Yang; Xin Yang; Lanjun Shao; Yuanyuan Wang; Jianjun Chen; Shiyuan Deng (Frontiers in Plant Science)
Tobacco (Nicotiana tabacum L.) is well-known as an economic crop whose quality is evaluated according to its aroma quality. Researchers have found that selenium application can increase the aroma quality of tobacco, but until now, its mechanism is still unclear. So a field experiment was conducted to investigate the regulatory effect of the trace element selenium on enhancing aroma substances in flue-cured tobacco leaves. We compared selenium content, aroma precursors, non-volatile organic acids (NVOAs) content, and neutral aroma substances in tobacco upper leaves that applying three selenium fertilizer types (sodium selenite, organic selenium and nano-selenium) with three levels of pure selenium application rates (5.24 g·hm-2, 10.48 g·hm-2, and 15.72 g·hm-2) through foliar spraying. The results showed that the neutral aroma substances and NVOAs content were significantly increased. Metabolomics analysis of NVOAs showed that biosynthesis of phenylpropanoids pathway was significantly enriched. This indicates that selenium application may be able to regulate the accumulation of phenylpropane degradation products by regulating these NVOAs involved in the biosynthesis of phenylpropanoids pathway. Selenium content was significantly positively correlated with phenylpropane degradation products, NVOAs content, and phenolic compounds, while pyruvate was significantly down-regulated in each selenium application treatment. Therefore, it was speculated that selenium application could enhance the conversion of pyruvate into the biosynthesis of phenylpropanoids pathway. In summary, spraying organic selenium at 5.24–15.72 g·hm-2 or nano-selenium at 5.24–10.48 g·hm-2 could provide a suitable strategy for improving tobacco aroma quality.